Influenza Virus Infection Induces Host Pyruvate Kinase M Which Interacts with Viral RNA-Dependent RNA Polymerase - Miyake, Yukari; Ishii, Kosuke; Honda, Ayae (Frontiers in Microbiology, 2017)
Influenza virus RNA-dependent RNA polymerase (RdRp) is composed of three viral proteins, PB1, PB2 and PA and involved in both transcription and replication of negative strand genome RNA. This enzyme is multifunctional, with RNA polymerizing, cap binding, and endonuclease activities. RdRp synthesizes three different RNAs, complementary RNA (cRNA) and messenger RNA (mRNA) from the same template virus RNA (vRNA), and viral RNA (vRNA) from cRNA. To synthesize three RNAs by same enzyme RdRp requires conversion of RdRp function by host factor. Here, we performed yeast two-hybrid screening to identify this host factor. This screen revealed that pyruvate kinase M2 (PKM2) interacted with the influenza virus RNA polymerase PA subunit. We analyzed the interacting region, the expression level of this enzyme by western blotting, and the effects of siRNA transfection on influenza virus replication. The results showed that the C-terminal region of PKM2 interacted with the C-terminal region of the PA subunit, the expression level of pyruvate kinase increased with influenza virus infection time, and this enzyme was essential for influenza virus multiplication.